Relatıons Between Error Management Culture, Work Engagement And Organizational Creativity - Nanto, Zülküf; Özan, Mukadder Boydak (My University, 2024)
Purpose: The purpose of this research is to determine the effects of error management culture and work engagement behaviors on organizational creativity. Design/Methodology/Approach: In this study, the relational screening model was used since it was aimed to determine the relationship, relational change, effect and their degrees between at least two variables. In the 2018-2019 academic year, 747 teachers working in primary and secondary schools in five education regions in the city center of Elaziğ constitute the sample of the research. Relational screening model was used. The “Error Management Culture” scale was developed by the researcher. In the research, structural equation analysis was used to measure the effects of error management culture and work engagement behaviors on organizational creativity, and correlation analysis was used to measure the relationship between these concepts. In this research, a mediation analysis was conducted considering that the error management culture has a mediating role in the effect of work engagement behaviors on organizational creativity. Findings: In the research, it has been determined that the error management culture and the behaviors of work engagement have a significant relationship with organizational creativity. Error management culture and work engagement predict organizational creativity positively, significantly and weakly. In the mediation analysis, it was concluded that the error management culture partially mediate the effect of work engagement behaviors on organizational creativity. Highlights: In schools, practices that support teachers’ engagement to work should be included. In addition, in-service trainings and informative trainings on managing errors should be given to administrators and teachers.
Keywords: Work engagement; Error management culture; .Education; Organizatinal creativity; Structural equation analysis